Case Report: Popliteal artery entrapment syndrome as a cause of deep vein thrombosis and subsequent popliteal artery occlusion - Lee, Sangho; Hwang, Deokbi; Yun, Woo-Sung; Huh, Seung; Kim, Hyung-Kee (Frontiers in Surgery, 2024)
Background: Popliteal artery entrapment syndrome (PAES) is a relatively rare cause of arterial insufficiency in young and physically active individuals; however, deep vein thrombosis (DVT) can develop in association with PAES. Case report: A 47-year-old man presented with a 6-day history of left leg swelling and discomfort which was diagnosed as DVT extending to the distal femoral vein and pulmonary embolism on computed tomography (CT). PAES was not suspected at this time, and the patient was administered anticoagulants for 1 year. Two years after the DVT diagnosis, the patient developed sudden-onset left calf claudication for one week. Repeat CT angiography showed popliteal artery (PA) occlusion caused by PA displacement from an abnormally lateral insertion of the medial gastrocnemius head. A retrospective review of the initial CT scan confirmed this, as well as compression of the popliteal vein between the displaced medial head and the normal lateral head of the gastrocnemius. The patient eventually underwent myotomy and resection of the PA with an interposition graft. Conclusion: PAES should be included in the differential diagnosis of venous disease in younger patients who lack common predisposing factors.